The Role of Strigolactone in the Cross-Talk Between Arabidopsis thaliana and the Endophytic Fungus Mucor sp. - Rozpądek, Piotr; Domka, Agnieszka M.; Nosek, Michał; Ważny, Rafał; Jędrzejczyk, Roman J.; Wiciarz, Monika; Turnau, Katarzyna (Frontiers in Microbiology, 2018)
Over the last years the role of fungal endophytes in plant biology has been extensively studied. A number of species were shown to positively affect plant growth and fitness, thus attempts have been made to utilize these microorganisms in agriculture and phytoremediation. Plant-fungi symbiosis requires multiple metabolic adjustments of both of the interacting organisms. The mechanisms of these adaptations are mostly unknown, however plant hormones seem to play a central role in this process. The plant hormone strigolactone (SL) was previously shown to activate hyphae branching of mycorrhizal fungi and to negatively affect pathogenic fungi growth. Its role in the plant-endophytic fungi interaction is unknown. The effect of the synthetic SL analog GR24 on the endophytic fungi Mucor sp. growth, respiration, H2O2 production and the activity of antioxidant enzymes was evaluated. We found fungi colony growth rate was decreased in a GR24 concentration dependent manner. Additionally, the fungi accumulated more H2O2 what was accompanied by an altered activity of antioxidant enzymes. Symbiosis with Mucor sp. positively affected Arabidopsis thaliana growth, but SL was necessary for the establishment of the beneficial interaction. A. thaliana biosynthesis mutants max1 and max4, but not the SL signaling mutant max2 did not develop the beneficial phenotype. The negative growth response was correlated with alterations in SA homeostasis and a significant upregulation of genes encoding selected plant defensins. The fungi were also shown to be able to decompose SL in planta and to downregulate the expression of SL biosynthesis genes. Additionally, we have shown that GR24 treatment with a dose of 1 μM activates the production of SA in A. thaliana. The results presented here provide evidence for a role of SL in the plant-endophyte cross-talk during the mutualistic interaction between Arabidopsis thaliana and Mucor sp.